EFFECT OF DIFFERENT LEVELS AGROECOLOGICAL LOADS ON BIOCHEMICAL CHARACTERISTICS OF SOIL - A. V. Shchur; D. V. Vinogradov; V. P. Valckho (Юг России: экология, развитие)
Aim. To study the effect of different levels of agri-environmental loads on the enzymatic activity of the soil.Methods. Isolation of soil fauna was conducted by thermogradient. Ecological characteristics of soil biota community was determined by ecological indices. The enzymatic activity of soil under different crops and at different levels of agri-environmental loads in our experiments was determined by methods proven in the laboratory soil enzymology Institute of Experimental Botany name V.F. Kuprevich and Belorussian Research Institute for Soil Science and Agricultural Chemistry.Results. Community soil biota is polydominant character, as evidenced by the values of environmental indices. It does not set a significant impact on the community agrotechnological loads of soil micro and mesofauna. Absolute figures soil phosphatase activity averaged over all embodiments without recourse formation were higher by 63% compared with plowing. Invertase and catalase activity was much higher in stubble on all variants of the experiment and selection of terms. The content of peroxidase lower under pure steam. The laws have taken place in respect of peroxidase activity, marked for polifenoloksidase activity.Main conclusion. There was no major change in the ecological characteristics of soil biota. In the enzymatic activity of soil influenced by sampling time, fertilizer system, soil tillage methods and cultivated crops.